AB0406 A Study on Characteristics of Rheumatoid Arthritis Patients Achieving no Depression with 6 Months of Biologic Treatment. (9th June 2015) - Miwa, Y.; Takahashi, R.; Yanai, R.; Furuya, H.; Umemura, M.; Miura, Y.; Kasama, T.; Oh, K.; Toyoshima, Y.; Inagaki, K.; Hosaka, M.
Abstract : Background: It is known that rheumatoid arthritis (RA) is comorbid with various diseases, and especially concomitant depression is common with a high prevalence of approximately 20%. Even if RA disease activity is controlled, patients with persistent depression result in decreased ADL and QOL. Objectives: To study predictive factors for no depression status after using biologic agents for 6 months. Methods: The subjects were 333 RA patients treated with biologic agents. The following patient's characteristics were investigated: age, gender, the number of previous drugs, disease duration, the type of biologic agents, baseline steroid dosage, MTX dosage, serum RF, MMP-3, ACPA, TNF-α, and IL-6. For evaluation we used SDAI for RA disease activity, HAQ for ADL, Short Form (SF)-36 for QOL, and Hamilton Depression Rating Scale (HAM-D) or Self-rating depression scale (SDS) for depression status. No depression was defined by HAM-D7 or SDS39 after 6 months of treatment. The subjects were divided into two groups according to the presence or absence of depression, and a retrospective study was performed. We excluded 101 patients due to loss to 6-month follow-up and 39 patients due to incomplete data; therefore, we included 193 patients in the analysis. Results: Compared with a group of RA patients with depression (n=130), a group of patients without depression (n=63) had younger age (52.7±14.8 vs. 59.8±14.3, p=0.002), more males (p=0.046), lower baseline steroid dosage (3.2±3.1mg vs. 5.0±4.4mg, p=0.002), lower SDAI (22.9±12.8 vs. 29.5±15.2, p=0.002), lower HAQ (0.43±0.47 vs. 0.75±0.62, p<0.001), higher SF-36 (p<0.05 in all categories), lower SDS (38.2±8.5 vs. 46.7±9.6, p<0.001), and lower HAM-D (5.0±4.0 vs. 9.3±6.0, p<0.001). On the other hand, there was no significant difference on the types of biologic agents, the order of drugs used in the treatment, MTX dosage, disease duration, serum RF, MMP-3, ACPA, TNF-α, and IL-6. Conclusions: It was suggested that RA patients with lower disease activity, lower dosage of steroid, younger age, higher ADL and QOL, and lower depression scores at baseline are more likely to achieve no depression status with biologic treatment. Disclosure of Interest: Y. Miwa Grant/research support from: Astellas Pharm Inc., Mitsubishi Tanabe Pharma Corporation, AbbVie CK, Pfizer Japan Inc., Chugai Pharmaceutical Co., Ltd., and Eizai Co., Ltd., R. Takahashi: None declared, R. Yanai: None declared, H. Furuya: None declared, M. Umemura: None declared, Y. Miura: None declared, T. Kasama: None declared, K. Oh: None declared, Y. Toyoshima: None declared, K. Inagaki: None declared, M. Hosaka: None declared